Penerapan Metode Storytelling untuk Meningkatkan Keterampilan Berbicara - Tappi, Yulianus Minanga; Ramly; Wahab (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2025)
his study aims to apply the storytelling method to improve the speaking skills of students at Makassar State Senior High School 5. This study is a Classroom Action Research conducted in two cycles. The research subjects consisted of 30 students in grade XI. The instruments used included speaking skill tests and observations. Data analysis techniques were carried out quantitatively and qualitatively, by comparing the test results in cycles I and II using the percentage of improvement. The results showed that the application of the storytelling method significantly improved the speaking skills of students. In cycle I, the average score of students reached 65.5 with a mastery level of 16.7%. After improvements were made in cycle II, the average score increased to 84 with a mastery level of 93.3%. This improvement was seen in five main assessment aspects, namely fluency, pronunciation, intonation, grammar, and mastery of material. The storytelling method has been proven to not only improve technical aspects of speaking but also enhance students' confidence, creativity, and enthusiasm in learning. Storytelling can be used as an effective learning strategy to improve speaking skills while motivating students to be more active and creative in the learning process.